Upon the Midnight Clear - Kenyon, Sherrilyn 1965-; Copyright Paperback Collection (Library of Congress) (New York : St. Martin's Paperbacks, 2007)
Born on Olympus as a goddess, Leta knows nothing of the human world. But a ruthless enemy has driven her from the world of dreams and into the home of the only man who can help her: Aidan. Her immortal powers are derived from human emotion--and his anger is just the fuel she needs to defend herself.--From publisher's description.
"A dream-hunter novel"--Cover.
Keywords: Goddesses -- Fiction; Dreams -- Fiction; Fiction; Love stories